Between silence, letters and ideas: university reading and writing, our experience - Ríos Nava, Bernabé; Olivo Estrada, J. Ramón; Montaño Torres, Carmelina (Rastros Rostros, 2021)
In recent years we have witnessed the lack of skills and abilities of our first-year university students in thecomposition of academic writings. I confronted this scenario through a proposal of educational interventionduring the first semester in the Socioanthropology of Health class. The question is: how do we awaken interestand love for the composition of academics texts? This led me to: *) Build a theoretical foundation consistingof: 1) the constructivist approach from a cognitive perspective to highlight the development of thinking skills,meaningful learning and problem solving; 2) the sociocultural approach, to emphasize guided and cooperativelearning and reciprocal teaching; 3) the macrostructural theory of Kinstch and Van Dijk to cultivate the abilityto detect the keys of superstructural organization, and 4) the concept of academic literacy, to understand itsdynamic, teaching and possible solutions (strategies) that favor the transition of students towards a full participation of the discursive disciplinary culture; *) Implement various curricular modifications. The approachmotivated students to experience in body and soul the circumstances that a writer goes through; a readingand writing workshop was organized focused on the composition of two texts: autobiography and monograph.We conclude that the composition of the first text is adequate to initiate the students and accompaniment andgroup experiences are important components of the workshop.
Keywords: reading; writing; educational workshop; university students